Core Reactivity Analysis during Fuel Draining Process in the Molten Salt Fast Reactor - Puti Berkah Azurah; Dian Fitriyani; Indarta Kuncoro Aji (Universitas Andalas, 2022)
A study of the core criticality during the draining process of liquid fuel salt on Molten Salt Fast Reactor (MSFR) was done. Two accident scenario that causes the draining process were loss of freeze valve coolant and loss of secondary coolant. This study used basic design of the MSFR with the salt fuel compositions of LiF (77.5%) – ThF4 (19.985%) – 233UF4 (2.515%). The criticality calculation has been analyzed from the value of the effective multiplication factor obtained from Open MC (Monte Carlo base) calculation. The effective multiplication factor was calculated with a variation on the number of freeze valves open; 1, 8, and 16 valves. The calculation has resulted in the value of effective multiplication factor decreasing exponentially during the draining process. Results from this study could be used as basic for the future study of the accident condition in MSFR, since there are still many MSRs accident scenarios that still haven't been taken into account.